2019
DOI: 10.18632/aging.102043
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal stem cells acquire premature senescence and senescence associated secretory phenotype concurrent with persistent DNA damage after heavy ion radiation in mice

Abstract: Heavy ion radiation, prevalent in outer space and relevant for radiotherapy, is densely ionizing and poses risk to stem cells that are key to intestinal homeostasis. Currently, the molecular spectrum of heavy ion radiation-induced perturbations in intestinal stem cells (ISCs), that could trigger intestinal pathologies, remains largely unexplored. The Lgr5-EGFP-IRES-creERT mice were exposed to 50 cGy of iron radiation. Mice were euthanized 60 d after exposure and ISCs were sorted using fluorescence activated ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 60 publications
0
36
0
Order By: Relevance
“…In addition, intestinal epithelial organoids derived from aged mice also showed consistent upregulation of senescence markers such as SA-β-gal activity and p21 as compared to organoids derived from younger organisms (Uchida et al, 2018). Intestinal epithelial stem cells of old mice expressed enhanced mRNA levels of genes associated with cellular senescence and oxidative stress (Moorefield et al, 2017), and radiation exposure also induced premature cellular senescence and SASP phenotype in intestinal stem cells in vivo (Kumar et al, 2019b). It is thus evident that intestinal epithelial as well as stem cells exhibit age-dependent cellular senescence which can contribute to known functional alterations and disruption of gastrointestinal homeostasis.…”
Section: Gut Microbiome and Cellular Senescencementioning
confidence: 86%
See 1 more Smart Citation
“…In addition, intestinal epithelial organoids derived from aged mice also showed consistent upregulation of senescence markers such as SA-β-gal activity and p21 as compared to organoids derived from younger organisms (Uchida et al, 2018). Intestinal epithelial stem cells of old mice expressed enhanced mRNA levels of genes associated with cellular senescence and oxidative stress (Moorefield et al, 2017), and radiation exposure also induced premature cellular senescence and SASP phenotype in intestinal stem cells in vivo (Kumar et al, 2019b). It is thus evident that intestinal epithelial as well as stem cells exhibit age-dependent cellular senescence which can contribute to known functional alterations and disruption of gastrointestinal homeostasis.…”
Section: Gut Microbiome and Cellular Senescencementioning
confidence: 86%
“…It is thus evident that intestinal epithelial as well as stem cells exhibit age-dependent cellular senescence which can contribute to known functional alterations and disruption of gastrointestinal homeostasis. Moreover, the chronic SASP secreted by senescent intestinal cells can promote inflammatory environment and/or oncogenic transformation which can have harmful effects on gut permeability, immune activation as well as the gut microbiome composition (Kumar et al, 2019b;Sharma et al, 2021) (Figure 3). A breakthrough study demonstrated the effects of a dysbiotic gut in the development of SASP and its deleterious effects.…”
Section: Gut Microbiome and Cellular Senescencementioning
confidence: 99%
“…Data from this study are reminiscent of those from studies of intestinal stem cells from aged mice which demonstrate that senescent stem cells accumulate in intestinal crypts as mice age. (6,13) Accumulation of senescent cells is thought to contribute to decreased functional capacity, dysregulation of proliferation, and altered regenerative ability of ISC. (14,15) This leads us to consider that senescent cells could accumulate in small intestinal crypts following treatment with genotoxic agents, such as doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…And in the gut, ROS as a signal molecule, is majorly produced in mitochondrial, would stimulate inflammatory signal and plays a central role in colitis [54]. Overproduction of proinflammatory cytokine and ROS would amplify immune signal and exacerbate the breakdown of the epithelium [8,9,55]. Hence, controlling inflammation and oxidative is an effective way to treat IBD in clinical trials [8,56].…”
Section: Discussionmentioning
confidence: 99%